1999
DOI: 10.2134/agronj1999.915807x
|View full text |Cite
|
Sign up to set email alerts
|

Strip Intercropping Effects on Yield and Yield Components of Corn, Grain Sorghum, and Soybean

Abstract: 20 to 24% higher corn yields and 10 to 15% lower soybean yields in adjacent border rows. Strip intercropping of corn (Zea mays L.) and soybean [Glycine Water stress, light quality, and shading are among the max (L.) Merr.] and grain sorghum [Sorghum bicolor (L.) Moench] and soybean may be a viable alternative to monoculture cropping to factors that affect crop yields and yield components at help reduce soil erosion. Careful study of yields and yield components different growth stages. Sixty-three percent shadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 18 publications
13
40
0
Order By: Relevance
“…Plants of row 1 generated a second ear in 60% of the time of plants of row 1 and plants of row 12 generated a second ear 40% of the time (Table 3). Similar results were reported by Lesoing and Francis [20] and Ghaffarzadeh et al [26].…”
Section: Grain Yield Componentssupporting
confidence: 90%
See 2 more Smart Citations
“…Plants of row 1 generated a second ear in 60% of the time of plants of row 1 and plants of row 12 generated a second ear 40% of the time (Table 3). Similar results were reported by Lesoing and Francis [20] and Ghaffarzadeh et al [26].…”
Section: Grain Yield Componentssupporting
confidence: 90%
“…This response may be explained by findings of Lesoing and Francis [20,21] who reported that yield and its components increase as radiation interception increases. On the other hand, Andrade et al [7] and also Fisher and Palmer [22] have reported that irradiance reductions around the critical period may reduce the crop yields by 50%, whereas filling reduction may reduce yields by 25%.…”
Section: Grain Yield Componentsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, it was not treating or topological arrangement with which the highest gain was obtained ERT or greater, since there was a depression in bean yield compared to that obtained in CSMF. The decrease of 12-55% in performance or soya bean intercropped with maize has been reported by other authors (O'Callaghan et al, 1994;Lesoing and Francis et al, 1999;Matusso et al, 2014). The revised literature suggests that this is due to interspecific competition for light, water and nutrient advantage seen in corn.…”
Section: Resultssupporting
confidence: 78%
“…Higher grain y ield under sole cowpea compared to intercropping were reported by Chemeda [24]. Co mpetition for water, nutrients and shading are probably the two factors that reduced cowpea yield under high numbers of ma ize plants in Intercrop 1 [37]. There were no significant differences in the weight of cowpea seeds between treatments.…”
Section: Resultsmentioning
confidence: 62%